Global burden and trends of rotavirus infection-associated deaths from 1990 to 2019: an observational trend study - Du, Yuxia; Chen, Can; Zhang, Xiaobao; Yan, Danying; Jiang, Daixi; Liu, Xiaoxiao; Yang, Mengya; Ding, Cheng; Lan, Lei; Hecht, Robert; Zhu, Changtai; Yang, Shigui (Virology journal, 2022)
Rotavirus is the leading global pathogen of diarrhea-associated mortality and poses a great threat to public health in all age groups. This study aimed to explore the global burden and 30-year change patterns of rotavirus infection-associated deaths. Based on the Global Burden of Disease 2019 Study (GBD 2019), we analyzed the age-standardized death rate (ASDR) of rotavirus infection by sex, geographical region, and sociodemographic index (SDI) from 1990 to 2019. A Joinpoint regression model was used to analyze the global trends in rotavirus infection over the 30 years, SaTScan software was used to detect the spatial and temporal aggregations, and a generalized linear model to explore the relationship between sociodemographic factors and death rates of rotavirus infection. Globally, rotavirus infection was the leading cause of diarrheal deaths, accounting for 19.11% of deaths from diarrhea in 2019. Rotavirus caused a higher death burden in African, Oceanian, and South Asian countries in the past three decades. The ASDR of rotavirus declined from 11.39 (95% uncertainty interval [95% UI] 5.46-19.48) per 100,000 people in 1990 to 3.41 (95% UI 1.60-6.01) per 100,000 people in 2019, with an average annual percentage change (AAPC) (- 4.07%, P < 0.05). However, a significant uptrend was found in high-income North America (AAPC = 1.79%, P < 0.05). The death rate was the highest among children under 5 years worldwide. However, the death rates of elderly individuals over 70 years were higher than those of children under 5 years in 2019 among high, high-middle, middle, and low-middle SDI regions. Current health expenditure, gross domestic product per capita, and the number of physicians per 1000 people were significantly negatively correlated with death rates of rotavirus. Although the global trends in the rotavirus burden have decreased substantially over the past three decades, the burden of rotavirus remained high in Africa, Oceania, and South Asia. Children under 5 years and elderly individuals over 70 years were the populations most at risk for rotavirus infection-associated deaths, especially elderly individuals over 70 years in relatively high SDI regions. More attention should be paid to these areas and populations, and effective public health policies should be implemented in the future.